Autoimmune Encephalitis and Paraneoplastic Neurological Syndromes with Progressive Supranuclear Palsy-like Manifestations - Naoki Yamahara; Akira Takekoshi; Akio Kimura; Takayoshi Shimohata (Brain Sciences)
Background: Advances in diagnostic procedures have led to an increasing rate of diagnosis of autoimmune encephalitis or paraneoplastic neurological syndrome (AE/PNS) among patients with progressive supranuclear palsy (PSP)-like manifestations. Methods: In this narrative review, we first discuss the clinical characteristics of AE/PNS in comparison to those of PSP, followed by a discussion of diagnosis and treatment. Results: The antibodies involved in these conditions include anti-IgLON5, -Ma2, and -Ri antibodies, each of which has a characteristic clinical presentation. The steps in the diagnosis of AE/PNS in patients with PSP-like manifestations include (i) suspicion of AE/PNS based on clinical presentations atypical of PSP and (ii) antibody detection measures. Methods used to identify antibodies include a combination of tissue-based assays and confirmatory tests. The primary confirmatory tests include cell-based assays and immunoblotting. Treatments can be divided into immunotherapy and tumor therapies, the former of which includes acute and maintenance therapies. Conclusions: One of the major challenges of diagnosis is that existing reports on PSP-like patients with AE/PNS include only case reports, with the majority discussing antibodies other than anti-IgLON5 antibody. As such, more patients need to be evaluated to establish the relationship between antibodies and PSP-like manifestations.